Effects of Early Myocardial Postnatal Maturation on Tolerance to Atrial Tachycardia With Altered Loading Conditions: An in vivo Swine Model - Fortin-Pellerin, Etienne; Khoo, Nee S.; Coe, James Y.; Mills, Lindsay; Cheung, Po-Yin; Hornberger, Lisa K. (Frontiers in Pediatrics, 2020)
Postnatal maturation of the myocardium starts shortly after birth and could affect how clinicians should provide hemodynamic support during this transition. Our aim was to assess the impact of postnatal maturation on tolerance to tachycardia with altered loading condition in a piglet model. Methods: We report three series of experimentations. Six groups of landrace cross neonatal piglets (NP)(1-3 days) and young piglets (YP)(14-17 days) were assigned to tachycardia (NP, YP), tachycardia and hypervolemia (NPV, YPV) or tachycardia and increased afterload (NPA, YPA) groups (n = 7/group). Under anesthesia, a pressure catheter was placed in the left ventricle and pacing wire in the right atrium. NPV and YPV groups had 60ml/kg of normal saline infused over 20 minutes. NPA and YPA had balloon sub-occlusion of the descending aorta. Heart rate was increased by 10bpm increments to 300bpm. Left ventricular output was measured by echocardiography. Results: NP maintained left ventricular output throughout the pacing protocol but the YP did not (p < 0.001). With volume loading both NPV and YPV maintained their output with tachycardia. Although increased afterload resulted in reduced output during tachycardia in NPA (p = 0.005), there was no added impact on output in YPA. Interestingly, 4 of 7 NPV had significant desaturation at 300bpm (baseline 99.7% vs. 300bpm 87.9%, p = 0.04), associated with a right to left shunt through the patent foramen ovale which resolved immediately on cessation of pacing. Conclusions: Early postnatal maturation is associated with improved myocardial tolerance to increased afterload and poor tolerance of tachycardia, the latter of which may be alleviated by increasing intravascular volume. These data could translate into the development of better strategies to optimize cardiac output at these early development ages.